Health-related Quality of Life in Patients on Hemodialysis and Peritoneal Dialysis: a Meta-Analysis of Iranian Studies (Iranian Journal of Kidney Diseases, 2015)
Introduction. Health-related quality of life (HRQOL) is an index to calculate wellbeing of patients and is an important concept in patients with end-stage renal disease.  There are many studies calculating HRQOL for patients on different treatment modalities of end-stage renal disease. Pooling reports from Iran, this systematic review aimed to measure the HRQOL in patients on hemodialysis and peritoneal dialysis using meta-analysis techniques. Materials and Methods. Four databases including PubMed and Scopus in English and the SID and IranMedex in Persian were searched. Based on the inclusion criteria, 26 English and Persian-language articles reporting HRQOL in the scales between zero and 100 (or scales convertible to this range) for hemodialysis or PD were included in the meta-analysis. Results. The mean HRQOL scores ranged between 34.40 and 69.16 for hemodialysis reports and between 38.00 and 65.70 for PD reports. The pooled quality of life scores for hemodialysis and PD were 52.257 and 52.722, respectively (t = 0.928, P = .36). Conclusions. The results showed that HRQOL in patients using hemodialysis and peritoneal dialysis were not significantly different. Similar studies in other countries had found similar results.